MAGMATIC AND POST-MAGMATIC SIGNIFICANCE OF CHROMITITE AND ASSOCIATED PLATINUM-GROUP MINERALS (PGM) IN THE EASTERN KHOY OPHIOLITIC COMPLEX (NW IRAN) - Azimzadeh, Amir M.; Zaccarini, Federica; Moayyed, Mohsen; Garuti, Giorgio; Thalhammer, Oskar A.R.; Uysal, Ibrahim; Mirmohammadi, Mirsaleh (Ofioliti, 2011)
The Khoy ophiolites are one of the largest Iranian ophiolitic complexes and are characterized by a very complicate geology, consisting of several ophiolites with different ages and geodynamic settings of formation. Few small lenticular and irregular bodies of podiform and schlieren type chromitites have been recognized in the Khoy ophiolites, occurring in the serpentinized mantle peridotites. They have massive and nodular textures. According to their chromite composition, the Khoy chromitites can be classified as Al-rich and fall clearly in the field of podiform chromitites. The magmatic chromite composition of the podiform chromitites of the Khoy ophiolites suggests that they crystallized from a MORB type melt in an extensional regime. The Khoy chromitites were altered during ocean floor metamorphisms and no magmatic silicates were preserved. The composition of chlorite occurring in the silicate matrix or in contact with chromite has been used as a geothermometer. The estimated temperatures possibly reflect the effects of low-grade metamorphism. The Khoy chromitites have very low total platinum group elements (PGE) concentration with a predominance of Os + Ir + Ru over Rh + Pt + Pd. Consistently with the geochemical data, they contain few platinum group minerals (PGM) of Ru, Ir and Os. Laurite is the most common PGM along with a minor Ir-Cu sulfide, possibly cuproiridsite, osmium and erlichmanite. Most of the PGM are magmatic in origin. They crystallized in a narrow range of temperature, around 1000oC, at relatively low sulfur fugacity and in the absence of fluids. This observation is consistent with formation of the chromitites in a mid-oceanic ridge (MOR) rather than in a supra-subduction zone (SSZ).